Pengaruh Kualitas Pelayanan Informasi dan Customer Experience Terhadap Kepuasan Pelanggan di Yogyakarta International Airport - Arisma Hermi; You She Melly Anne Dharasta (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Service quality is an important aspect in a service company. In addition to providing high-quality services that result in customer satisfaction, companies also need to give customers a memorable experience when using the service. The success of a business depends on how the company is able to satisfy and delight customers. Therefore, these two variables are one of the determining factors in how customer satisfaction can be achieved. This study aims to examine the effect of Information Service Quality and Customer Experience on Customer Satisfaction at Yogyakarta International Airport both partially and simultaneously. The research design used is quantitative research using statistical data analysis based on numbers obtained from questionnaires which are then processed using SPSS software. The sample in this study were 99 customers at Yogyakarta International Airport using purposive sampling technique. From the results of the respondents' answers that have been collected, data analysis techniques are carried out including instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing and determination coefficient tests. The research results obtained show that there is an effect of Information Service Quality (X1) on Customer Satisfaction (Y) as evidenced by a significance value of 0.017 < 0.05 and T count 2.422 > T table 1.98498. In addition, there is an effect of Customer Experience (X2) on Customer Satisfaction (Y) as indicated by a significance value of 0.000 < 0.05 and T count 6.833 > T table 1.98498. As for the simultaneous Information Service Quality (X1) and Customer Experience (X2), it shows a significant positive effect on Customer Satisfaction (Y) as evidenced by the significance value of 0.000 <0.05 and F count 95.470> F table 3.091. The results of the determination coefficient test show that Information Service Quality (X1) and Customer Experience (X2) contribute to Customer Satisfaction (Y) by 66.5% and the remaining 33.5% is influenced by other variables. It can be concluded that all H₀ is rejected and Hₐ is accepted in the three hypotheses in this study.